PENGEMBANGAN DESAIN PELATIHAN KEWIRAUSAHAAN SOSIAL BAGI PEREMPUAN RAWAN SOSIAL EKONOMI - Muhamad Nur Hasan Fadli; Lina Favourita; Denti Kardeti (Politeknik Kesejahteraan Sosial Bandung, 2022)
Socio-economically vulnerable women are adult women who are married, single or widowed and do not have enough income to be able to meet their daily basic needs. This socio-economic vulnerable woman comes from a poor family who has daily activities in processing pandan woven crafts as a livelihood. The design of this social entrepreneurship training aims to address the problems of socio-economic vulnerable women in Grenggeng Village so that they are more independent and effective in the process of assisting social entrepreneurship training. This research was conducted to obtain an empirical picture (initial conditions, formulating needs, implementation, and results of implementation) of the design of social entrepreneurship training. In this research activity using a type of qualitative research and participatory action research (PAR) methods, namely the existence of special involvement from participants and assistants giving feedback to each other both questions and answers during the process. This study involved 6 (six) participants divided into 3 (three) assistants and 3 (three) socioeconomically vulnerable women from the beginning to the end of the research process. Based on the results of the research and data analysis, it can be concluded that the Development of a Social Entrepreneurship Training Design is effective and able to increase the independence of socio-economic vulnerable women in a series of good and systematic process of chicken pandan craft training that is carried out on an ongoing basis starting from the stages: preparation, identification of needs, criteria and indicators of success, implementation of training, evaluation, and partnerships. This is evidenced by the increased independence of the six research subjects namely AS, LS, SP, AC, PL, and BC. Development of Social Entrepreneurship Training Design can be one of the references in perfecting the concept of social entrepreneurship training and can contribute to providing the development of social entrepreneurship training designs in social work practices with poverty.